THE ROLE OF Amorphophallus titanum (Becc.) IN CULTURE, ECOSYSTEMS AND SCIENCE - Novitasari, Naintyn; Ruyani, Aceng; Yanti, Fitri April (Universitas Medan Area, 2025)
Amorphophallus titanum (Becc.) is one of the rare species of flora in Indonesia, this flora is also an endemic plant to the island of Sumatra that naturally grows along Bukit Barisan and is mostly found in the western slopes such as Bengkulu, Kerinci, Palembang, Bukit Tinggi. This research was conducted to determine the role of the rare flower A. titanum (Becc) which is not found in all regions in Indonesia. The method used in this article is a literature study by analyzing or reviewing several journal articles. This review provides information that shows the role of A. titanum (Becc.) in culture, its role in ecosystems, its role in science and its challenges and opportunities in the future. Conservation efforts of A.titanum not only protect its species, but also preserve the cultural values associated with its presence. A. titanum is not only important for maintaining the sustainability of its own species, but also for protecting tropical forest ecosystems that are home to a diverse range of flora and fauna. A. titanum (Becc.) also plays an important role as a subject of scientific research to understand various aspects of life, ecosystems, and environmental conservation efforts.